Blogging as a Means of Crafting Writing. (28th November 2012) - Lacina, Jan; Griffith, Robin
Abstract: The purpose of this article is to explore ways in which blogs can support literacy communities while developing a writing community. Examples of how a classroom teacher uses blogs to strengthen the writing process is described.